PALYNOLOGICAL STUDY OF THE JAMBI SUB-BASIN, SOUTH SUMATRA - Christina Ani Setyaningsih; Eko Budi Lelono; Iskandar Firdaus (Scientific Contributions Oil and Gas, 2015)
The palynological study of the Jambi Sub-basin, South Sumatera is carried out to construct biostratigraphy of the identifi ed formation. The palynological analysis provides an age interpretation as well as environment of depositional interpretation. The study uses outcrop samples which were collected from Merangin River, Muara Jernih and Mengupeh areas. The age of the studied sediment ranges from Early to Middle Miocene. The top Middle Miocene age is identifi ed by the occurrence of pollen Florschuetzia levipoli and Florschuetzia meridionalis, whilst the base of Early Miocene is marked by the appearance of nannoplankton Sphenolithus compactust. The studied sediment cropping out at the Merangin River and Muara Jernih area interpreted as Talang Akar Formation was deposited in a lower delta plain to delta front during Early Miocene. In the Mengupeh area, this sediment shifted landward into upper delta plain to lower delta plain environment during Middle Miocene.